Graves’ ophthalmopathy – thyroid eye disease - Dagna Siedlecka (Journal of Education, Health and Sport, 2019)
Graves’ disease (GD) is an autoimmune disorder that affects thyroid. It is caused by antibody, named thyroid-stimulating immunoglobulin (TIS) that acts like thyroid stimulating hormone (TSH), resulting in thyroid hormone overproduction – condition called hyperthyroidism. TSH receptors are located on thyroid cells, but also on ocular fibroblasts – that’s why Graves’ disease can result in ocular manifestations also known as Graves ophthalmopathy (GO). Typically patients with hyperthyroidism are affected by ophthalmopathy, but it can occur in hypothyroid or euthyroid patients as well. It is estimated that 20-35% of patients with Graves' disease develop thyroid eye disease. In most cases symptoms are mild and do not require specialist treatment. Decision about therapy should be made considering severity of the disease and it is influence on quality of life.